Botswana : Background Papers and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1995)
This Background Paper and Statistical Appendix describes economic and financial developments in Botswana during 1993-94. Although real GDP in Botswana recovered somewhat to 2.5 percent in 1993/94, compared with a decline of 1.5 percent in 1992/93, this outcome represented a decline in real GDP per capita for the second consecutive year. The government sector continued to expand relatively fast as the civil service continued to grow fairly rapidly, leading to an increasing share in the nonmining GDP, which rose from 34.8 percent in 1992/93 to 36.1 percent in 1993/94.